Demografi dan Kepuasan Kerja Perawat Puskesmas di Kabupaten Kotawaringin Barat - Togar Hasudungan Manurung; Martha Irene Kartasurya; Ayun Sriatmi (Jurnal Kesehatan Indonesia, 2022)
Nurse job satisfaction is a considerable concern among health practitioners due to the diverse results of the study. From a preliminary study, it was found that the job satisfaction of public health centers (PHC) staffs in West Kotawaringin Regency were still low. The purpose of the study was to analyze demographic factors that affected the PHC of nurse job satisfaction. This research was conducted using a cross-sectional design. The research population of nurses in health centers was affordable to a stable internet network. Subjects’ recruitment was carried out in 10 from 18 existing PHC in West Kotawaringin Regency. A total of 95 subjects who met the inclusion criteria filled out the questionnaires which was distributed electronically. Data analysis was performed by multiple logistic regression. PHC job satisfaction was 41,1%. Higher job satisfaction was found in male nurses, undergraduate education levels/Ners, service periods of 11 to 20 years, nurses with civil service status, and worked in inpatient PHCs. There was no significant association between gender (0,161), education (0,757), length of work (0,761), employment status (0,104) with job satisfaction. There was a significant relationship between the type of health center (0,019) and job satisfaction. Factors related to job satisfaction together are employment status and PHC type.